E-CRM is a foundation of accelerating economical stability in Indian banking industry - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
In the history of Indian banking system, the last decade has turned into the different direction towards technological advancement and modern application with the help of information technology which control the entire world and playing as a role of pioneer in any kind of industry to make the work is easy and flexible. Now a day?s all the industries mainly the industry of banking survives and reaching the path of success by adopting innovated technologies and software to compete others in its industry. Today?s Information technology has changed the business in the form of smart and fast accessible concern with excellence in their work. No one can avail the best result without the help of technology in banking mainly on e-CRM. Application of tools and techniques like e-CRM, has slightly improved in all sector of banking and its increased hope of investors, customers and government which is mainly used to maximize the financial stability. This study is mainly focus the method of banking transaction after implementing the e- CRM concept and how it?s affecting growth of financial stability of a bank in India.